Prospects of a settlement with the Afghan Taliban: Exit, peace and governance from the Taliban perspective - Mona Kanwal Sheikh; Amina Khan (Danish Institute for International Studies (DIIS), 2019)
This report provides a backdrop for identifying conflict resolution initiatives in support of a settlement with the Taliban in Afghanistan. It reviews the multifaceted peace processes, both past and present, and provides insights into the most recent developments among the Taliban. Based on secondary sources and interviews with Taliban leaders, commanders and foot soldiers, the report highlights the development of an unprecedented momentum calling for the international community to identify ways to support the Afghan peace and reconciliation process.
Keywords: 300